Preferences and Attitude toward English Phonetics Learning: The perspectives of Indonesian EFL Learners - Nindya Agustina Savitri; Firdaus Andrianto (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
English learners should aware of English sounds, more specifically English phoneme, to comprehending the English language accurately. In order to completing the goal this research aimed to find out students’ preferences and attitude of English Education Program in Universitas Brawijaya. This was a descriptive quantitative research by using a survey design. The participants of this study were 103 (a hundred and three) students of batch 2015 to 2017 in English Language Education Program. The researcher used adopted questionnaire which consist of 8 items preferred themes and 19 statements of attitude in phonetic as the instrument by Lintunen and Makilahde (2013). This research was analyzed using SPSS program. The result of this study revealed student’s preference and attitudes toward phonetics learning. The most preferred topic chosen by the participants are the vowel systems (28.20%), speech rhythm and accent difference (27.20%), and intonation analysis (26.20%). The students performed a positive attitude toward English phonetic learning that can improve their skill in English especially in their pronunciation (98.1%). It is concluded that the students thought English Phonetics is important to increase their knowledge and their skill in learning English. The researcher suggested for future researcher, they can conduct the research by considering the correlation between pronunciation in English phonetics and speaking skill in English language